Anesthetic management of a patient with situs inversus posted for laparoscopic cholecystectomy - Hazarika, Plabon; Das, Prabir Pranjal (International Journal of Research in Medical Sciences, 2017)
Situs inversus totalis is a rare congenital visceral malrotation anomaly that results from disturbances in establishment of left-right asymmetry. It is an autosomal recessive condition, in which organs are transposed from their normal location to the opposite side of the body and the predicted incidence is one in 10, 000 among the general population. In a patient with situs inversus totalis, not just the diagnosis of any acute abdomen pathology is difficult but equally challenging is the anesthetic management during the respective surgical procedure. We are reporting a patient who had situs inversus totalis and was operated for laparoscopic cholecystectomy under general anesthesia, and endotracheal tube as an airway conduit. Though the problems related to such patients are mainly of surgical feasibility, an anesthesiologist must be aware of the associated problems of both, situs inversus and the surgical procedures. The present case report lays an emphasis on the potential difficulties during anesthetic management and its various implications in a remote area in North East India with resource limitations. To the best of our knowledge, we report the first case from a remote are in North East India of a successful laparoscopic cholecystectomy in a patient with situs inversus totalis under general anesthesia which was uneventful.